Business strategy of salted egg agro-industry to achieve sustainable competitive advantage - Sumekar, W.; Al-Baarri, A. N.; Setiadi, A. (Diponegoro University, 2021)
Business strategy is an effort to achieve a sustainable competitive advantage in an agro-industry. The research objective on salted egg agro-industrial center is to identify a model for business development. The advantages of salted duck eggs have been recognized by people in south east asian countries and east asian countries. This observational research was conducted on 105 salted egg agro-industries in Brebes Regency. Data on 22 variables of quantitative strategic planning were collected through interviews using a questionnaire. Strategy formulation framework method was applied to determine specific alternative strategies to reach sustainable competitive advantage The results showed that the salted egg agro-industry were not supported by the availability of duck eggs and upstream industry (50.58%) although most consumers were fond of salted egg due to its taste (52.38%), texture (58.10%), and price (71,43%). The salted egg agro-industry was in the aggressive position. The best strategy concept for business policy development was market penetration The market penetration strategy was chosen, namely increasing promotion and sales volume. Market penetration strategy is suggested to be the mod-el for empowering salted egg agro-industry and agro-industrial commodities in general so that the activ-ity of duck farming and upstream industry can be leveraged.